2020
DOI: 10.1016/j.omtn.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

KLF5-Modulated lncRNA NEAT1 Contributes to Tumorigenesis by Acting as a Scaffold for BRG1 to Silence GADD45A in Gastric Cancer

Abstract: Long noncoding RNAs (lncRNAs), genomic “dark matter,” are deeply involved in diverse biological processes. The lncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) is a highly participatory lncRNA; however, its roles in gastric cancer (GC) remain largely unexplored. Here, we demonstrated that the expression of NEAT1 was significantly increased and negatively correlated with prognosis in GC. Subsequent experiments confirmed that KLF5 can induce NEAT1 expression by binding to the NEAT1 promoter region. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…In line with our data, KLF5 was also discovered as a transcription factor to facilitate lncRNAs expression in other malignancies. For instance, KLF5-activated lncRNA NEAT1 accelerated gastric cancer progression via serving as a scaffold for BRG1 to down-regulate GADD45A expression [ 34 ]. KLF5-regulated lncRNA RP1 contributed to cell proliferation and metastasis in breast cancer through suppressing p27kip1 translation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our data, KLF5 was also discovered as a transcription factor to facilitate lncRNAs expression in other malignancies. For instance, KLF5-activated lncRNA NEAT1 accelerated gastric cancer progression via serving as a scaffold for BRG1 to down-regulate GADD45A expression [ 34 ]. KLF5-regulated lncRNA RP1 contributed to cell proliferation and metastasis in breast cancer through suppressing p27kip1 translation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA nuclear paraspeckle assembly transcript 1 (NEAT1) is an essential component of the nuclear paraspeckle substructure [9]. Particularly, NEAT1 is a pro-oncogenic factor that plays a positive role in various solid tumors, such as liver, prostate, and gastric cancers, as well as renal cell carcinomas and glioma [10][11][12][13][14]. In glioma, NEAT1 has been found to regulate tumor progression via mTOR signaling pathway [15].…”
Section: Introductionmentioning
confidence: 99%
“…Of tens of thousands of metazoan lncRNAs discovered from cDNA libraries and RNAseq data by high throughput transcriptome projects, only a handful of lncRNAs have been functionally characterized. The investigations on this small cohort of lncRNAs have demonstrated that these noncoding transcripts can serve as scaffolds or guides to regulate protein-protein or protein-DNA interactions [28][29][30][31] or can modulate post-translational modification of nonhistone proteins [32]. Moreover, lncRNAs are capable of controlling microRNAs (miRNAs) [33][34][35], and function as enhancers to influence gene transcription, when transcribed from the enhancer regions (enhancer RNA) [36][37][38] or their neighboring loci (noncoding RNA activator) [39,40].…”
Section: Long Non-coding Rna Structures and Functionsmentioning
confidence: 99%